2007
DOI: 10.1038/sj.bjc.6603718
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic growth signalling, DNA replication licensing, and survival are linked in prostate cancer

Abstract: Activation of mitogen/extracellular-signal-regulated kinase kinase 5/extracellular signal-regulated kinase-5 (MEK5/ERK5) growth signalling is coupled to increased cell proliferation in prostate cancer (PCa). Dysregulation of the DNA replication licensing pathway, a critical step in growth control downstream of transduction signalling pathways, is associated with development of PCa. In this study we have investigated linkages between the MEK5/ERK5 pathway and DNA replication licensing during prostate carcinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
4
27
1
1
Order By: Relevance
“…Given the mitotic effect of MEK5/ERK5 signaling in CaP, we explored its link with DNA replication licensing factors using a combination of clinical samples and in vitro cell model (Dudderidge et al, 2007). Significant associations between Gleason grade and the number of cells traversing G 1 phase was observed (P ¼ 0.001), with high ERK5 levels associated with both an increase in replication licensed but noncycling cells (Mcm2 þ ve/Ki67Àve; P ¼ 0.01) and accelerated cell cycle progression (shortened G 1 phase; P ¼ 0.005), phenotype consistent with increasing proliferative potential.…”
Section: Discussionmentioning
confidence: 99%
“…Given the mitotic effect of MEK5/ERK5 signaling in CaP, we explored its link with DNA replication licensing factors using a combination of clinical samples and in vitro cell model (Dudderidge et al, 2007). Significant associations between Gleason grade and the number of cells traversing G 1 phase was observed (P ¼ 0.001), with high ERK5 levels associated with both an increase in replication licensed but noncycling cells (Mcm2 þ ve/Ki67Àve; P ¼ 0.01) and accelerated cell cycle progression (shortened G 1 phase; P ¼ 0.005), phenotype consistent with increasing proliferative potential.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are competent to reenter the cell division cycle and reside in a G1 extended or arrested state (Todorov et al, 1994;Endl et al, 2001;Stoeber et al, 2001;Williams and Stoeber, 2007). It was shown that increase of this cell population was significantly associated with high tumor grades in renal cell carcinoma, prostate cancer and oligodendroglioma (Dudderidge et al, 2005(Dudderidge et al, , 2007Wharton et al, 2007) and with tumor metastasis in colorectal cancer (Nishihara et al, 2008). We also observed higher labeling indexes for MCM2, MCM3 and MCM7 than that for Ki67 in MB, indicating the presence of this licensed but nonproliferative MB cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, the MAPKs selectively phosphorylate cellular targets, leading to regulation of gene expression and biologic events such as proliferation, differentiation, and apoptosis (Ghosh et al, 2005). There are reports that demonstrate that the MEK5/ ERK5 pathway was involved in tumorgenesis and malignancies (Mehta et al, 2003;Dudderidge et al, 2007;Li et al, 2008). Dudderidge et al (2007) showed that the induction of …”
Section: Discussionmentioning
confidence: 99%
“…There are reports that demonstrate that the MEK5/ ERK5 pathway was involved in tumorgenesis and malignancies (Mehta et al, 2003;Dudderidge et al, 2007;Li et al, 2008). Dudderidge et al (2007) showed that the induction of …”
Section: Discussionmentioning
confidence: 99%